Efficacy and Safety Assessment of Antifungal Prophylaxis with Posaconazole Using Therapeutic Drug Monitoring in Pediatric Patients with Oncohematological Disorders—A Single-Centre Study - Karolina Liszka; Paweł Marschollek; Dawid Przystupski; Jowita Frączkiewicz; Monika Mielcarek-Siedziuk; Igor Olejnik; Zuzanna Gamrot; Natalia Haze; Agnieszka Kwella; Paulina Zalewska; Matylda Resztak; Marek Ussowicz; et al. (Journal of Fungi)
Introduction: Posaconazole is recommended for prophylaxis in pediatric immunocompromised patients. Due to its variability in bioavailability and drug-to-drug interactions, EBMT recommends regimens based on therapeutic drug monitoring (TDM). Materials and methods: In total, 171 oncohematological pediatric patients on posaconazole prophylaxis were included. Full pharmacokinetic posaconazole profiles were assessed in 51 children. The efficacy and safety of posaconazole was evaluated by measuring the drug concentration, with dose modification attempted in patients with suboptimal results. The influence of modifying factors on the posaconazole plasma concentration (PPC) was investigated. Results: An insufficient PPC was the main issue, but no significant increase in prophylaxis failure was reported. The modification of the dosage resulted in the optimization of PPC in 50% of patients. No significant correlation between age, gender, diagnosis or the posaconazole dosage and the PPC was found. HCT, total parenteral nutrition and diarrhea were associated with a lower PPC. Hypoalbuminemia was related to both higher and lower PPC. The concomitant administration of specified drugs significantly impacted the PPC. Conclusions: TDM allows the identification of patients receiving non-optimal treatment and offers an opportunity to improve the efficacy and safety of the therapy. However, further research involving larger patient groups and longer observation periods are needed to determine the optimal dosing and target PPC in pediatric patients.